Oczekiwania rodziców z klasy średniej wobec szkoły i nauczyciela = Middle-class parents` expectations towards school and the teacher - Nyczaj-Drąg, Mirosława (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article describes, analyses, and interprets partial results of the study on middle-class parents? experience related to the early education of their children and the subjective meanings that they ascribe to this education. At the beginning of the text, the author presents children?s and adolescents? education as one of the most important values in the opinion of the contemporary middle-class parents. Next, the author presents empirical data (their description, analysis, and interpretation), gathered through narrative interviews, about the meanings ascribed by this group of parents to children`s early education, which meanings parents connected with their expectations towards school and the teacher.
Keywords: rodzice; klasa średnia; oczekiwania; nauczyciel wczesnej edukacji; szkoła; parents; middle class; expectations; the early school education teacher; school